2021
DOI: 10.3390/diagnostics11030403
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of C-Reactive Protein-to-Albumin Ratio in Head and Neck Cancer: A Meta-Analysis

Abstract: The C-reactive protein-to-albumin ratio is a proven prognostic predictor of nasopharyngeal carcinoma. However, the role of the C-reactive protein-to-albumin ratio in other head and neck cancers remains unclear. This meta-analysis explored the prognostic value of the C-reactive protein-to-albumin ratio in head and neck cancers. A systematic search was conducted. Outcomes of interest included overall survival, disease-free survival, and distant metastasis–free survival. The hazard ratio with 95% confidence inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Recently, researchers have used the CRP/Alb ratio to predict the clinical prognosis of patients with cancer. A high CRP/Alb ratio is considered a marker of adverse clinical outcomes in tumors [10,11]. Likewise, in our study, a high CRP/Alb ratio was closely related to disease severity and progression and was an independent risk factor for disease progression in patients with severe COVID-19.…”
Section: Disease Markerssupporting
confidence: 75%
See 1 more Smart Citation
“…Recently, researchers have used the CRP/Alb ratio to predict the clinical prognosis of patients with cancer. A high CRP/Alb ratio is considered a marker of adverse clinical outcomes in tumors [10,11]. Likewise, in our study, a high CRP/Alb ratio was closely related to disease severity and progression and was an independent risk factor for disease progression in patients with severe COVID-19.…”
Section: Disease Markerssupporting
confidence: 75%
“…Based on these characteristics, clinical researchers speculate that the CRP/Alb ratio, a compound index, is a promising new biomarker in patients with cytokine storm syndrome. Previous studies have shown that CRP/Alb ratio is a promising prognostic biomarker for critically illness [9], cancers [10,11], and Kawasaki disease [12]. Based on current data, CRP/Alb ratio could predict adverse clinical outcomes.…”
Section: Introductionmentioning
confidence: 97%
“… 4 Therefore, a large number of peripheral inflammatory and/or nutritional indexes, such as hemoglobin (HB), platelet (PLT), monocyte (MONO), lymphocyte (LYMPH), neutrophil (NEUT), albumin (ALB), prealbumin (PALB), C-reactive protein (CRP), CRP to ALB ratio (CAR), NEUT to LYMPH ratio (NLR), PLT to LYMPH ratio (PLR), prognostic nutritional index (PNI), and systemic immune-inflammation index (SII), have been reported to be associated with tumor prognosis. 5 - 12 However, nutritional and/or inflammatory status may influenced by various non-cancer-related conditions, which may lead to biased results. Moreover, these peripheral indexes are deficient in some respects, and the results for some indexes are still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Increased evidence has shown that host immunity and systemic inflammation play an important role in cancer angiogenesis and progression, although the exact pathogenesis is not thoroughly understood 5 , 6 . Accumulated studies have shown that many inflammation-based scores, including the neutrophil-to-lymphocyte ratio, Glasgow prognostic score, lymphocyte-to-monocyte ratio, platelet-to-lymphocyte ratio, and C-reactive protein to albumin ratio, are associated with cancer survival and prognosis 7 , 8 . Identification of precise and available prognostic indicators may optimize the management of patients suffering from HNC.…”
Section: Introductionmentioning
confidence: 99%